Factors Influencing Cryptocurrency Retention Of Use In Indonesia - Mahotma, I Made Adwesta; Permana, Gusi Putu Lestara; Mimaki, Caren Angellina (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research investigates the determinants of continued cryptocurrency usage in Indonesia by extending the Technology Acceptance Model (TAM). A quantitative research approach was employed using a survey method to collect data from cryptocurrency users located in Java and Bali. Respondents were selected through purposive sampling to ensure that participants had prior experience using cryptocurrency. The collected data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software to assess the reliability and validity of the measurement model, as well as to examine the structural relationships among variables through bootstrapping techniques.  The results indicate that perceived ease of use and perceived usefulness both have a positive and significant influence on cryptocurrency retention of use, confirming their importance in post-adoption behavior. In addition, cryptocurrency knowledge plays a moderating role in the model. Specifically, higher levels of cryptocurrency knowledge strengthen the relationship between perceived usefulness and retention of use, while weakening the effect of perceived ease of use. This finding suggests that knowledgeable users tend to prioritize functional benefits and investment advantages over system simplicity when deciding whether to continue using cryptocurrency. From a practical perspective, the study provides valuable insights for cryptocurrency platform developers, educators, and policymakers. Enhancing system functionality, improving user education, and developing supportive regulatory frameworks may help promote sustainable and long-term cryptocurrency usage in Indonesia.